Rocuronium continuous infusion for profound neuromuscular blockade: a systematic review and meta-analysis - Couto, Mafalda (2019)
Rocuronium is a muscle relaxant with increased use, because of the binding relation with the reversal agent sugammadex. Its continuous infusion benefits the maintenance of deeper levels of neuromuscular blockade (NMB) ensuring an improved and stable solution for daily surgical anesthesia. This is systematic review on current approaches on rocuronium infusion and monitoring parameters when using rocuronium continuous infusion for profound muscle relaxation (0-2 posttetanic count).